Biological therapies in lung cancer treatment: using our immune system as an ally to defeat the malignancy. (4th May 2019) - Filipska, Martyna; Pedraz-Valdunciel, Carlos; Chaib, Imane; Rosell, Rafael
ABSTRACT: Introduction : Biological therapies, with immunotherapy leading the field, have arisen as one of the quickest expanding areas of research for cancer treatment in the last few years. The clear benefits for patients are undeniable, satisfying the long-awaited necessity of a target-specific therapy. However, its full potential remains still unexploited due to a lack of response in a majority of patients and pending reliable biomarkers. Areas covered : This review provides a summarizing view of the current biological therapies for lung cancer, focusing on immunotherapy – including immune checkpoint inhibitors, adoptive cell therapy and vaccines available in clinical/pre-clinical settings or currently in development. A thorough analysis of the technical and functional differences among all therapies is provided, along with a critical discussion of prospective treatments and potential biomarkers. Expert opinion : The use of immunotherapy in the treatment of cancer has provided clear benefits for patients. Still, exploitation of the full potential of immune checkpoint inhibitors alone or in combination, or adoptive cell therapies is hampered by, amongst other reasons, the lack of reliable biomarkers and possible adverse immune effects. We postulate that the development of liquid biopsy-based diagnostics will help to overcome these limitations in the near future.